Market Reforms at the Zero Lower Bound - Cacciatore, Matteo (IMF Working Papers; Working Paper, 2017)
This paper studies the impact of product and labor market reforms when the economy faces major slack and a binding constraint on monetary policy easing. such as the zero lower bound. To this end, we build a two-country model with endogenous producer entry, labor market frictions, and nominal rigidities. We find that while the effect of market reforms depends on the cyclical conditions under which they are implemented, the zero lower bound itself does not appear to matter. In fact, when carried out in a recession, the impact of reforms is typically stronger when the zero lower bound is binding. The reason is that reforms are inflationary in our structural model (or they have no noticeable deflationary effects). Thus, contrary to the implications of reduced-form modeling of product and labor market reforms as exogenous reductions in price and wage markups, our analysis shows that there is no simple across-the-board relationship between market reforms and the behavior of real marginal costs. This significantly alters the consequences of the zero (or any effective) lower bound on policy rates.